Nuclear energy: A pathway towards mitigation of global warming. (January 2022) - Mathew, M.D.
Abstract: Global warming is the ongoing rise in the average temperature of Earth's climate system. Over the past 50 years, the average temperature has increased at the fastest rate in recorded history due to uncontrolled generation of greenhouse gases. Nuclear power is low carbon energy, and it is contributing on a large scale to a low carbon economy and a green energy grid. 442 nuclear power reactors are operating worldwide generating 393 GWe of electricity providing continuous and reliable low carbon power. Nuclear electricity accounts for 11% of total global electricity generation, and this amounts to a third of the low-carbon electricity produced in the world. New innovations are taking place which make nuclear power a more affordable and attractive energy option. These include advances in large reactors, emerging technologies such as advanced fuel and small modular reactors, engineering breakthroughs extending the operational lifetime of existing reactors, and new developments in materials and better waste management. Fast breeder reactor technology has become a commercial reality and it helps not only in generating electricity, but also in producing more fuel than it consumes, besides burning nuclear waste more efficiently compared to any of the existing commercial reactor technologies. The Sun's energy is generated by nuclear fusion. Mastering nuclear fusion technology can guarantee energy security in terms of clean, safe and affordable energy. Nuclear fusion, and plasma physics research of very complex nature are being carried out in many countries. Fusion reactions have been successfully demonstrated although for a fraction of a second and without demonstrating a net gain of electric power. The world's largest international fusion reactor facility called ITER is in an advanced stage of construction with the aim of demonstrating the scientific and technological success of fusion energy research for commercial production. Fusion fuel is plentiful and easily accessible. It is expected that fusion energy is the pathway towards energy security for thousands of years. Nuclear fission and fusion reactors do not emit greenhouse gases into the atmosphere and play a major role in mitigating climate change. Highlights: Average temperature of the Earth's climate system increased due to uncontrolled generation of greenhouse gases. Decarbonizing electricity generation essential to combat climate change. Nuclear power plants produce no greenhouse gas emissions during their operation. Fast reactor technology enables more efficient use of uranium resources. Nuclear fusion technology, can provide unlimited clean, safe and affordable energy.